The Legal Status and Juridical Authority of the Hakam in the Islamic Law: An Analysis of Syiqaq Cases in the Exegesis of Fakhruddin al-Razi - Ishak, Sufriadi; Nidal, Ahmad; umar, Fazlon; Abubakar, Alauddin; Nusir, Firman (El-Usrah: Jurnal Hukum Keluarga, 2025)
Household conflict (syiqaq) is a recurrent phenomenon with the potential to culminate in divorce, producing adverse consequences for spouses, children, and the broader social environment. Addressing syiqaq with fairness and wisdom is therefore an urgent necessity, particularly by recognizing the role of the hakam (mediator) as prescribed in Islamic teachings. This study examines the concept, legal status, qualifications, authority, and procedural role of the hakam as outlined in Fakhruddin al-Razi’s exegesis (Tafsir al-Razi). Employing a textual and content analysis methodology within a thematic (maudhu‘i) interpretative framework, the research analyzes relevant Qur'anic verses and al-Razi’s commentary concerning hakam in the context of syiqaq. Al-Razi underscores the hakam as a just mediator, typically drawn from among pious individuals or members of the disputing families. Two primary perspectives on the hakam's authority are identified: (1) possessing full decisional authority, and (2) serving solely as a non-binding intermediary. The mediation process involves structured dialogue, mutual consultation, and efforts to arrive at an optimal resolution, whether through reconciliation or separation. The hakam model remains pertinent in contemporary settings, provided it is adapted in accordance with the principles of justice and equity. Collaboration between state institutions and community actors is essential to enhancing the effectiveness of mediation practices and mitigating the incidence of divorce. Accordingly, mediation via the hakam represents a balanced and equitable approach to resolving familial disputes, safeguarding the integrity of the family unit as a foundational element of society.